Artificial Intelligence Applications in Middle School Mathematics Lessons: A Qualitative Study Based on Student Opinions (Third Sector Social Economic Review, 2026)
There are various perspectives on the integration of artificial intelligence into education. These range from computer systems acting like intelligent teachers, facilitating decision-making processes in educational settings, improving the quality of teaching, learning, and assessment, developing new strategies for learning processes, adapting classrooms to student profiles, and creating diverse content related to students' interests. The fact that artificial intelligence applications are believed to have such a broad impact on education highlights that it is a subject worthy of serious research.This physical research was conducted to determine the measurements of artificial intelligence applications in mathematics branches among middle school students. For this purpose, the participants of the research consisted of 74 middle school students selected from middle schools in the Mamak district of Ankara province using a convenient sampling method, a type of purposeful sampling. The data for the study were obtained using a semi-structured interview form created by the researcher. The obtained data were analyzed using content analysis. The results of the research show that the opinions of middle school students regarding the application of artificial intelligence in mathematics lessons consist of the following main conclusions: the current use of artificial intelligence applications, which artificial intelligence applications have an impact, how artificial intelligence applications should be used, which mathematics topics require artificial intelligence applications, and the benefits and drawbacks of using artificial intelligence applications. Based on these findings, it is recommended that the mathematics curriculum be updated to incorporate artificial intelligence-based applications, and that middle school mathematics teachers receive the necessary training to implement this curriculum.
Keywords: Middle school, artificial intelligence, artificial intelligence applications, middle school students, qualitative research.